Robustness of a class of variance balanced designs against the loss of one or two blocks - Mandal S.,; Ghosh D.K.,; Bagui S.C., (Utilitas Mathematica, 2013)
A class of variance balanced designs is obtained with (v - 1) treatments starting from a balanced incomplete block design with v treatments. The robust criteria of this class of variance balanced designs are obtained against the loss of any one or two blocks. Robust variance balanced designs are also obtained for another class of variance balanced designs. This article shows that the covered designs are fairly robust against the loss of one or two blocks.